Rancang Bangun Sistem Pemasaran Produk Ornamen Bangunan Di Kabupaten Gowa Berbasis Android - H, M. Hasrul; Hariani, Hariani; Yahya, Yahya (Jurusan Sistem Informasi Universitas Islam Negeri Alauddin Makassar, 2023)
The industrial era is forcing almost all sectors and business players to replace their service and product marketing systems with conventional to digital technology, likewise in building ornament artisans. An ornament is a decoration made to beautify a house or building both outside and inside the room; the function of the ornament is also to provide air circulation in the room to get fresh air. This research aims to make it easier for building ornament artisans to market their products more broadly. The approach used in developing this software is a prototype that allows interaction between system developers and system users to overcome incompatibilities between developers and users. The results of the development of an Android-based building ornament marketing application can display information related to building ornaments, making it easier for potential customers to see the type and specifications of the desired ornament.